2015
DOI: 10.1530/eje-14-0810
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of DLK1, differential expression of CYP11B1, CYP21A2 and MC2R, and lack of INSL3 distinguish testicular adrenal rest tumours from Leydig cell tumours

Abstract: Objective: Testicular adrenal rest tumours (TARTs) are a common finding in patients with congenital adrenal hyperplasia (CAH). These tumours constitute a diagnostic and management conundrum and may lead to infertility. TART cells share many functional and morphological similarities with Leydig cells (LCs), and masses consisting of such cells are occasionally misclassified as malignant testicular tumours, which may lead to erroneous orchiectomy in these patients. Design: In this study, we aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…For example, Rossato et al used the immunohistochemistry analysis to demonstrate that INSL3 expression was negative or decreased in Leydig cell tumor samples, but strongly and diffusely positive in normal Leydig cells and Leydig cell hyperplasia [31]. Lottrup et al also confirmed that INSL3 could not be detectable in testicular adrenal rest tumors [32]. Kaplan-Meier analysis of SNAP91 in the GSE7696 dataset showed that glioblastoma patients with high expression of SNAP91 exhibited a higher survival ratio compared with those having low levels of SNAP91 [33].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rossato et al used the immunohistochemistry analysis to demonstrate that INSL3 expression was negative or decreased in Leydig cell tumor samples, but strongly and diffusely positive in normal Leydig cells and Leydig cell hyperplasia [31]. Lottrup et al also confirmed that INSL3 could not be detectable in testicular adrenal rest tumors [32]. Kaplan-Meier analysis of SNAP91 in the GSE7696 dataset showed that glioblastoma patients with high expression of SNAP91 exhibited a higher survival ratio compared with those having low levels of SNAP91 [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a clinical need for differential diagnostic markers that can differentiate between both pathologies exists. Bilateralism of the tumours ( 25 , 30 ), presence of Reinke crystals ( 1 , 5 , 25 , 31 , 31 , 32 , 33 , 34 ) and expressions of synaptophysin, Inhibin α, CD56, androgen receptor, DLK1, INSL3, CYP11B1, CYP21A2 and MC2R ( 33 , 34 , 35 , 36 ) have all been studied as potential markers, but none of these markers individually can reliably discriminate TARTs from LCTs. We found significantly higher gene expressions of GATA3 and GATA6 in TARTs compared to LCTs with good discriminative potential.…”
Section: Discussionmentioning
confidence: 99%
“…CYP21A2, CYP11B1 and NR0B1/DAX1 mutations), the malignancy risk for the testis is estimated as being low (37,38,39). 46,XY patients with 21-hydroxylase deficiency and 11b-hydroxylase deficiency may develop TARTs, which can compromise fertility and sometimes be mistaken for Leydig cell malignancy; but TARTs are benign (37,40) and can be controlled by proper treatment (41). Importantly, testosterone overproduction as seen in some of these defects seems not to be associated with increased germ cell cancer risk (15,37).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%